Significance of Ultrasound Examination in Clinical Diagnosis of Nephroangiopathies in Latent Diabetes Type 2 - Dilshodov A.D.; Sobirov A.A. (Scholars Digest Publishing, 2023)
Currently, diabetic nephropathy (DN) is one of the most common causes of the development of terminal chronic renal failure (CRF) and dramatically reduces the overall and cardiovascular survival of patients with diabetes mellitus (DM). The need to use expensive methods of renal replacement therapy for the treatment of patients in the terminal stage of DN, as well as social adaptation, makes the problem significant not only in the medical, but also in the socio-economic aspect. The proportion of DN in the overall structure of renal pathology depends on the regional epidemiological characteristics of the disease. The scale of this problem at the national level has been clarified only recently and turned out to be quite comparable with global data.
Keywords: arterial hypertension, blood pressure, mean blood pressure, angiotensin II, glomerular basement membrane, diastolic blood pressure, diabetic glomerulosclerosis, diabetic nephropathy, coronary heart disease, insulin-dependent diabetes mellitus.